Leadership in Democracy - Brooker, P. author. aut Link
IX, 273 p.
Keywords: This 2nd edition includes a new chapter on presidential leadership and foreign policy, and has expanded its coverage of Schumpeter's and other leadership models of democracy. Its focus, however, remains on pioneering political leadership in the electoral, governmental, legislative, and administrative sectors of the US and British democracies.